2016
DOI: 10.31235/osf.io/kxghv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding the Financial Knowledge Gap: A New Dimension of Inequality in Later Life

Abstract: To understand the relationship between financial knowledge and financial behaviors, it is important to understand the financial knowledge gap -the distance between objectively and subjectively measured financial knowledge. Overestimating one's financial knowledge can lead to risky financial behaviors and economic vulnerability. To date, limited empirical work has examined how the gap between one's perception of their own financial knowledge and their actual knowledge varies across the life course. We analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Previous studies have revealed that subjective financial knowledge has a positive relationship with financial well-being (Riitsalu and Murakas, 2019;Woodyard, 2013); financial behavior (Allgood and Walstad, 2013;Deenanath et al, 2019;Hilgert et al, 2003;Robb and Woodyard, 2011;Sivaramakrishnan et al, 2017;Seay and Robb, 2013;Tang and Baker, 2016;Xiao et al, 2014); and financial decisions (Khan et al, 2017). Even though previous studies have indicated that both objective and subjective financial knowledge are important to financial behavior to which they contribute different roles, several studies have revealed that subjective financial knowledge is more adequate for explaining financial decisions and behaviors than objective financial knowledge (Robb and Woodyard, 2011).…”
Section: Subjective Financial Knowledgementioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies have revealed that subjective financial knowledge has a positive relationship with financial well-being (Riitsalu and Murakas, 2019;Woodyard, 2013); financial behavior (Allgood and Walstad, 2013;Deenanath et al, 2019;Hilgert et al, 2003;Robb and Woodyard, 2011;Sivaramakrishnan et al, 2017;Seay and Robb, 2013;Tang and Baker, 2016;Xiao et al, 2014); and financial decisions (Khan et al, 2017). Even though previous studies have indicated that both objective and subjective financial knowledge are important to financial behavior to which they contribute different roles, several studies have revealed that subjective financial knowledge is more adequate for explaining financial decisions and behaviors than objective financial knowledge (Robb and Woodyard, 2011).…”
Section: Subjective Financial Knowledgementioning
confidence: 98%
“…Financial literacy is described using various concepts that continue to be studied and developed over time. Previous studies have conceptualized financial literacy using multivariables (Atkinson and Messy, 2012;Huston, 2010;Hung et al, 2009;Khan et al, 2017;Lusardi and Mitchell, 2013;Xiao et al, 2014;Priyadharshini, 2017;Dewi et al, 2020). In recent years, the conceptualization of financial literacy has increasingly evolved along with the development of dynamic financial issues.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations